Crystal structures and crystal chemistry of compounds M5-pT4+pO14: dedicated to Prof. F. Liebau on the occasion of his 65th birthday - Eysel, Walter; Lambert, Ulrich; Mayer, Β. E.; Renkenberger, Christof; Nuber, Bernhard (Zeitschrift für Kristallographie, 1992)
Der Artikel Crystal structures and crystal chemistry of compounds M5-pT4+pO14 wurde am 1. November 1992 in der Zeitschrift Zeitschrift für Kristallographie - Crystalline Materials (Band 201, Heft 1-4) veröffentlicht.